2000
DOI: 10.1007/pl00008834
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological forcing of plankton dynamics in a large and deep continental European lake

Abstract: The timing of various plankton successional events in Lake Constance was tightly coupled to a largescale meteorological phenomenon, the North Atlantic Oscillation (NAO). A causal chain of meteorological, hydrological, and ecological processes connected the NAO as well as winter and early spring meteorological conditions to planktonic events in summer leading to a remarkable memory of climatic effects lasting over almost half a year. The response of Daphnia to meteorological forcing was most probably a direct e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
221
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(242 citation statements)
references
References 50 publications
17
221
1
Order By: Relevance
“…Most previous studies often regarded the development of spring phytoplankton spring as a period cycle of seasonal events and emphasized the importance of large-scale climatic fluctuation on the development of spring bloom (Semetacek, 1990;Yin et al, 1997;Straile, 2000;Iriarte and Purdie, 2004;Miller and Harding, 2007). Some studies have confirmed the expected earlier onset of the spring bloom under warming conditions (Rees et al, 1999;Peeters et al, 2007a), which agree with the frequently reported earlier onset of spring events reported from terrestrial ecosystems (e.g.…”
Section: Discussionsupporting
confidence: 75%
“…Most previous studies often regarded the development of spring phytoplankton spring as a period cycle of seasonal events and emphasized the importance of large-scale climatic fluctuation on the development of spring bloom (Semetacek, 1990;Yin et al, 1997;Straile, 2000;Iriarte and Purdie, 2004;Miller and Harding, 2007). Some studies have confirmed the expected earlier onset of the spring bloom under warming conditions (Rees et al, 1999;Peeters et al, 2007a), which agree with the frequently reported earlier onset of spring events reported from terrestrial ecosystems (e.g.…”
Section: Discussionsupporting
confidence: 75%
“…Madhudatrap et al (1996) triggered the germination of six Baltic Sea zooplankton species (four copepods, two cladocerans) by temperature increase in the laboratory. The temperature dependence of zooplankton spring growth must have consequences for the timing and extent of the clear-water phase, as predicted by a recent model for Lake Constance (Scheffer et al 2001) and by an analysis of field data using the present day climate variability (Straile 2000).…”
Section: Motivationmentioning
confidence: 98%
“…Climate change is already affecting a wide variety of ecosystems (Walther et al 2002), including aquatic ones (Edwards et al 2002;Edwards and Richardson 2004;Fromentin and Planque 1996;Straile 2000;Straile and Adrian 2000), and will increasingly continue to do so if the prevailing predictions of further greenhouse warming are fulfilled. Already, now, the Baltic Sea is characterised by a strong geographic, seasonal, and interannual variability of all relevant hydrographic variables, which are closely connected to the atmospheric forcing in the region (Matthä us and Schinke 1994; Lehmann et al 2002).…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, European lake ecosystems are influenced by variations in the North Atlantic Oscillation (e.g. Gerten & Adrian, 2000Livingstone & Dokulil, 2001;Straile, 2000;Straile & Adrian, 2000;Weynhenmeyer et al, 1999Weynhenmeyer et al, , 2002. In addition, lakes have the potential to reveal changes and homogeneous trends even at relatively short (i.e.…”
Section: Introductionmentioning
confidence: 99%